KELOMPOK IBU MENYUSUI DENGAN AREOLA DAN ROLLING MASSAGE DALAM MENGHADAPI 1000 HARI PERTAMA KEHIDUPAN - Desmawati . (Poltekkes Kemenkes Denpasar, 2020)
The first 1000 days of human life involving 730 days after baby was born. Many babies are given a breast milk substitute that is not good for the baby. The best food for the baby is breast milk because that contains the complement needed by the baby. The problem for breatfeeding mothers after gave birth is there is no production of breast milk or obstacle in ejection of breast milk. This happens because of lack of knowledge of mother and family, lack of support from their family, or very busy to take interventions to facilitate bresftfeeding. Areola-Rolling (ARO) massage is a combination massage on the areola and backbone in breastfeeding mother which helps increase production and smooth ejection of breast milk. Knowledge is important for doing areola and rolling (ARO) massage because the massage is not only physiologically, but need appropriate place to do massage for increasing breast milk production and ejection. Besides, family support is also important to do ARO massage due to require the help of others in conducting backbone massage (areola massage) and mother should to be happy. If there is no these conditions can make disease of the mother and baby such as mastitis, fever, dehydration of the baby, hiperbiliruninemia, and the risk of breast cancer. The purpose of this community service is to increase breast milk production and ejection. Also motivating the health workers to help mother and add ARO massage in operating standards in activity daily living in the post partum area. Method; used the demonstration of ARO massage. Results of this community service revealed that from 12 breastfeeding mothers who receving the ARO massage after 2 hours post partum make their breast milk smooth and increase their knowledge. Conclusion the ARO massage can increase production and ejection of the breast milk in post partum mother 2 hours after gave birth. The ARO massage is suggested for mother by normally labor 2 hours after gave birth.